2022
DOI: 10.1158/1541-7786.mcr-21-0612
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK Inhibitor Peposertib Amplifies Radiation-Induced Inflammatory Micronucleation and Enhances TGFβ/PD-L1 Targeted Cancer Immunotherapy

Abstract: Radiation therapy is the most widely used cancer treatment and improvements in its efficacy and safety are highly sought-after. Peposertib (also known as M3814), a potent and selective DNA-PK inhibitor, effectively suppresses the repair of radiation-induced DNA double-strand breaks (DSB) and regresses human xenograft tumors in preclinical models. Irradiated cancer cells devoid of p53 activity are especially sensitive to the DNA-PK inhibitor, as they lose a key cell cycle checkpoint circuit and enter mitosis wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…Due to the dependence of AZD7648 on type I IFN responses, it would be interesting to combine this drug with immunomodulatory drugs that enhance the type I IFN response. Additionally, the DNA-PKi peposertib enhanced RT-induced TGFβ/PD-L1-targeted immunotherapy in mice, further supporting the combination of DNA-PKi, RT, and immunotherapy ( 69 ).…”
Section: Dna-pk Inhibitorsmentioning
confidence: 74%
See 1 more Smart Citation
“…Due to the dependence of AZD7648 on type I IFN responses, it would be interesting to combine this drug with immunomodulatory drugs that enhance the type I IFN response. Additionally, the DNA-PKi peposertib enhanced RT-induced TGFβ/PD-L1-targeted immunotherapy in mice, further supporting the combination of DNA-PKi, RT, and immunotherapy ( 69 ).…”
Section: Dna-pk Inhibitorsmentioning
confidence: 74%
“…Further, studies have shown that DNA damage-induced upregulation of PD-L1 by cisplatin or ionizing radiation was suppressed by co-administration with ATRi agents ( 67 ). DNA-PK inhibitors seem to upregulate PD-L1 ( 69 ) along with WEE1 inhibitors ( 2 ) and Chk1/2 inhibitors ( 70 , 71 ), likely by preventing the repair of double-stranded DNA breaks, which activates STAT1/3 signaling through ATM/ATR/Chk1 kinases, resulting in an upregulation of PD-L1 levels ( 60 ).…”
Section: Ddri-induced Upregulation Of Pd-l1mentioning
confidence: 99%
“…50 metaphase spreads per treatment were scored for chromosomal aberrations. For spectral karyotyping (SKY) analysis, fixed cells were processed as described elsewhere [ 32 ]. Ten metaphase spreads were analyzed per treatment condition.…”
Section: Methodsmentioning
confidence: 99%
“…An ongoing phase I trial (NRG-HN008), is evaluating the use of peposertib, a DNA-dependent protein kinase RT, radiation therapy; LRC, locoregional control; LRF, locoregional failure; PFS, progression-free survival; OS, overall survival; AE, adverse events (DNA-PK) inhibitor, with RT in LA-HNC patients with a contraindication to cisplatin [68]. Preclinical have demonstrated that this agent suppresses repair of radiation-induced DNA double-strand breaks, increases PD-L1 expression on cancer cells, and enhances inflammatory signaling [69]. Another class of agents includes second mitochondria-derived activator of caspases (SMAC) mimetics, which antagonize apoptosis inhibitor proteins (IAPs) and exhibit radiosensitizing effects via caspase-dependent and CD8 T cell-dependent pathways [70••].…”
Section: Novel Targeted Therapiesmentioning
confidence: 99%